ESTIMATION OF THE TIME OF THE VESSEL'S ARRIVAL AT PORT - Onyshchenko, S. P.; Koskina, Y. A. (Science and Transport Progress, 2019)
Purpose. The paper aims at the assessment of the probability of the vessel’s arrival at the port at a specified time interval considering the different combination of the voyage charter-party (C/P) terms and their wordings. Methodology. The structure of the vessel's time in port was formed considering the C/P terms and their wordings. The time intervals for which it is actual to estimate the time of arrival were defined on the basis of the theory of transport processes and systems. The normal distribution law was used to estimate of the probability of a vessel's arrival at a port at a specified time interval. Findings. The probability of the vessels arrival at the port of loading in the C/P in question was searched in three most actual situations: 1) the vessel's opening date is known; 2) the vessel's arrival to the port of discharging on previous C/P is known and 3) the vessels position on the passage to the port of discharging in previous voyage is known. For these three situation were estimate the probability of the duration of the time elements from the opening point and present position points to the port of loading in the C/P in question far as the C/P terms indicate the beginning the duration of the laytime. Originality. For the first time the vessel's time in port was structured considering the C/P terms and their possible wordings, their impact on the time in port was determined, and the probability of vessel's arrival at specified time intervals was searched. Practical value. The obtained results can be used in voyage planning (during fixing the C/P and further voyage performance) by estimation the duration of the time in port considering the C/P terms and wordings of the beginning and duration of laytime and time of the vessel's arrival.